ANALYSIS OF OXYTOCIN MASSAGE AND BREAST CARE ON SMOOTH BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Nadia Fitri; Siti Mardhatillah Musa; Atnesia Ajeng (PT. Radja Intercontinental Publishing, 2026)
Breast milk is the most comprehensive biological nutrition for infants, yet the coverage of exclusive breastfeeding in postpartum mothers has not yet reached global targets. Delays in breast milk production, maternal stress, and lack of lactation support are factors that influence breastfeeding success. This study aims to analyze the effectiveness of oxytocin massage and breast care on smooth breast milk production in postpartum mothers. The study used a qualitative research method with a systematic literature review approach. The study population was scientific articles discussing oxytocin massage, breast care, and breast milk production in postpartum mothers in 2020–2025. The study sample consisted of 20 articles selected purposively based on inclusion and exclusion criteria. The research instruments included an article search sheet, inclusion and exclusion criteria, and a data extraction matrix. Data analysis was conducted using content analysis and narrative synthesis. The results showed that oxytocin massage and breast care significantly increased breast milk production, facilitated milk letdown, reduced maternal stress, and improved breastfeeding comfort. The combination of the two interventions provided more optimal results than either intervention alone. The conclusion of this study is that oxytocin massage and breast care are non-pharmacological interventions that are effective, safe, and easy to implement to support the success of exclusive breastfeeding in postpartum mothers